Frequency and histoclinic pathology of malignant and potentially malignant disorders of oral cavity in Chile - Aitken-Saavedra, Juan Pablo; Valdivia, Angélica Diaz; Adorno-Farias, Daniela; Maturana-Ramirez, Andrea; Tarquinio, Sandra Chaves; Silva, Karine Duarte da; Fernandez-Ramires, Ricardo (Journal of Oral Diagnosis, 2017)
Introduction: Oral squamous cell carcinoma (OSCC) is the sixth most common type of cancer worldwide. Oral potentially malignant disorder (OPMD) represents a tissue where is more probably to occur a cancer in comparison with the apparently normal counterpart. Objective the purpose of this study was to determine the frequency and histoclinicpa- thology of these diseases in a Chilean population. This was a descriptive retrospective study. Material and Methods: Patients diagnosed with DPMO, OSCC and verrucous carcinoma (VC) treated in the Oral Medicine Clinic of University of Chile between 2005 and 2015 were selected, being revised the medical records and histopathological diagnoses. Results: From a sample of 241 patients, 60% were women and the mean age was 58 years. The prevalence of DPMO was 15%. The most prevalent of them was oral lichen planus (45%) follow by a 36% of leucoplakias, 16% of actinic cheilitis and 3% of erythroplakias. OSCC and VC accounted to 3.4% and 0.5% of the sample, respectively. The disease-free survival in 5 years for patients with OSCC was 39%. Conclusions: The results were similar to those reported by national and international studies must survival found was lower than reported.